Analysis of Employee Retention Programs and Talent Engagement to Prevent Employee Turnover in Organizations (Systematic Literature Review) - Primadi Candra Susanto; Zahara Tussoleha Rony (Asian Journal of Community Services, 2023)
Systematic Literature Review (SLR) is a process of identifying, assessing, and interpreting all available research evidence with the aim of providing answers to specific research questions. This article starts by determining the keyword search literature (search string) which is based on PICOC. An understanding of synonyms and word replacement alternatives will determine the accuracy of our literature search. Then the next step is determining the source (digital library) from the literature search. The writing structure of the SLR usually consists of 3 major parts, namely: Introduction, Main Body, and Conclusion. Preventing Employee Turnover in Organizations is proven to be important in existing organizations as evidenced by the existence of existing scientific articles relating to the variables in this scientific article. Recommendations for the continuation of the results of this research or scientific article, the continuation of the results of this research can be used as a reference and input material for further research in the future